Is a brief intervention effective in managing and decreasing severe alcohol use?. Issue 12 (December 2017) - Maples, Sarah; Johnson, Gary; Fiore, Dave
Abstract : EVIDENCE‐BASED ANSWER : Yes. Brief interventions decreased alcohol consumption by 19 to 51 g per week for at least a year in nondependent adults with excessive alcohol consumption (SOR: C, meta‐analyses of RCTs of disease‐oriented evidence).